Attachment anxiety predicts depression and anxiety symptoms following coronary artery bypass graft surgery. Issue 4 (6th October 2016) - Kidd, Tara; Poole, Lydia; Ronaldson, Amy; Leigh, Elizabeth; Jahangiri, Marjan; Steptoe, Andrew
Abstract : Objective: Depression and anxiety are associated with poor recovery in coronary artery bypass graft (CABG) patients, but little is known about predictors of depression and anxiety symptoms. Design: We tested the prospective association between attachment orientation, and symptoms of depression and anxiety in CABG patients, 6–8 weeks, and 12 months following surgery. Method: One hundred and fifty‐five patients who were undergoing planned CABG surgery were recruited. Patients completed questionnaires measuring attachment, depression, and anxiety prior to surgery, then 6–8 weeks, and 12 months after surgery. Results: Attachment anxiety predicted symptoms of depression and anxiety at both follow‐up time points, whereas attachment avoidance was not associated with depression or anxiety symptoms. The findings remained significant when controlling for baseline mood scores, social support, demographic, and clinical risk factors. Conclusion: These results suggest that attachment anxiety is associated with short‐term and long‐term depression and anxiety symptoms following CABG surgery. These results may offer important insight into understanding the recovery process in CABG surgery. Statement of contribution What is already known on this subject? Depression and anxiety symptoms are twice more likely to occur in coronary artery bypass graft (CABG) populations than in any other medical group. Depression and anxiety are associated with poor recovery following cardiac surgery. Predictors of depression and anxiety in CABG patients have been underexplored. What does this study add? This study highlights the importance of close interpersonal relationships on health. Attachment anxiety was prospectively associated with higher levels of depression and anxiety. These results add to understanding mechanisms linked to recovery following CABG.